The mindfulness workbook for OCD : a guide to overcoming obsessions and compulsions using mindfulness and cognitive behavioral therapy - Hershfield, Jon; Corboy, Tom, 1957- (New Harbinger Publications, 2020)
"Combining mindfulness practices with cognitive behavioral therapy (CBT), this fully revised and updated second edition of The Mindfulness Workbook for OCD offers practical and accessible tools for managing the unwanted thoughts and compulsive urges associated with obsessive-compulsive disorder (OCD). With this powerful workbook, readers will develop present-moment awareness, learn to challenge their own distorted thinking, and stop treating thoughts as threats and feelings as facts"--